Three-Layer Grating With the Enhanced Efficiency and Angular Bandwidth - Hongtao Li; Bo Wang (IEEE Photonics Journal, 2017)
We theoretically and numerically analyze and design a three-layer rectangular-groove dielectric grating based on modal design and rigorous numerical calculation. This three-layer grating device can only diffract the transverse electric (TE)- or transverse magnetic (TM)-polarized plane light in the first diffractive order with high efficiency. By use of modal design, three thicknesses of the three grating layers can be sketchily calculated based on physical theory of two-beam interference with the chosen duty cycle of 0.6 and period of 610 nm for an operating wavelength of 800 nm under Littrow appliance. In order to obtain three exact thicknesses of the grating layers, a rigorous vector coupled-wave analysis method based on the Maxwell's theory is used to numerically calculate the high diffraction efficiencies of 99.0% and 97.7% in the first order for TE and TM polarizations, respectively. Moreover, a wide spectral width of 67 nm and a broad angular width of 10.88° can be shown.